HARMONI PENDIDIKAN AGAMA ISLAM (PAI) DILINGKUNGAN PERGURUAN TINGGI PTU DAN PTAI - Haris, Abd (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2014)
Religion is as social rule share vital importancein influencing behaviour to all of followers in everyday life. It’s important role of this religion values. For example it can be seen in the view of Religion Education. Thinking about education,the existence is necessary for students, so that it can spring up and sturdy in their moral and character so that they rise to high intellectual of their moral and real correct and good behaviour. Behaviour of life believed in Indonesia still shadow strength of tradition of formalism and believe had not strength to correct moral distortion insocial life yet. Religion enemy does not only immorality, but also hardness and corruption.The day after day we ordinary hear and see progressively about the combustion, ruining, assault, murder, and bomb terror.Meanwhile, apathetic society progressively attack eradication of corruption which still circulate at some issues. As religion is recognized by nation, we ought to believe in to have contribution to lessen badness of social around us. It’s real, there is no marking that way.